Human Papillomavirus in Thai Women and Men with Anogenital Warts - Pornjarim Nilyanimit (2019)
© 2019 S. Karger AG, Basel. Objective: Anogenital warts are caused by human papillomavirus (HPV). Globally, HPV genotypes 6 and 11 are most often associated with anogenital warts. However, the diversity of HPV genotypes found in patients with genital warts in Thailand is unknown. The aim of this study was to investigate HPV-associated anogenital warts in the Thai population and to assess whether genotypes found are represented in the bivalent and quadrivalent HPV vaccine. Methods: This study included 206 anogenital swab samples from patients who were diagnosed with anogenital warts. Detection of HPV DNA was performed using polymerase chain reaction to amplify the L1 gene and sequencing. Results: HPV was identified in 88.3% (182/206) of the samples. The majority of HPV genotypes were low-risk genotypes HPV6 (36.9%) and HPV11 (36.4%), which represented the most common infection found in genital warts in this study. Conclusion: Immunization with the quadrivalent vaccine (HPV6, HPV11, HPV16, and HPV18) could potentially prevent genital warts caused by HPV infection.